TMPRSS2 expression dictates the entry route used by SARS-CoV-2 to infect host cells - Koch, Jana; Uckeley, Zina Maria; Doldan, Patricio; Stanifer, Megan; Boulant, Steeve; Lozach, Pierre-Yves (The EMBO journal, 2021)
Abstract SARS-CoV-2 is a newly emerged coronavirus that caused the global COVID-19 outbreak in early 2020. COVID-19 is primarily associated with lung injury, but many other clinical symptoms such as loss of smell and taste demonstrated broad tissue tropism of the virus. Early SARS-CoV-2?host cell interactions and entry mechanisms remain poorly understood. Investigating SARS-CoV-2 infection in tissue culture, we found that the protease TMPRSS2 determines the entry pathway used by the virus. In the presence of TMPRSS2, the proteolytic process of SARS-CoV-2 was completed at the plasma membrane, and the virus rapidly entered the cells within 10?min in a pH-independent manner. When target cells lacked TMPRSS2 expression, the virus was endocytosed and sorted into endolysosomes, from which SARS-CoV-2 entered the cytosol via acid-activated cathepsin L protease 40?60?min post-infection. Overexpression of TMPRSS2 in non-TMPRSS2 expressing cells abolished the dependence of infection on the cathepsin L pathway and restored sensitivity to the TMPRSS2 inhibitors. Together, our results indicate that SARS-CoV-2 infects cells through distinct, mutually exclusive entry routes and highlight the importance of TMPRSS2 for SARS-CoV-2 sorting into either pathway.